The Effects of Group Schema Therapy on Psychological Wellbeing and Resilience in Patients Under Substance Dependence Treatment - Majid Pourpashang; Shokoufeh Mousavi (Iran University of Medical Sciences, 2021)
Background: Low psychological resilience is an essential component in substance abuse relapse in individuals with substance use disorder. The present study aimed to investigate the effects of group schema therapy on psychological wellbeing and resilience in individuals under treatment with methadone and buprenorphine. Methods: The statistical population comprised 248 subjects with substance dependence under treatment in Samaa Addiction Treatment Clinic in Isfahan Province, Iran, in 2019. A sample of 40 patients was selected by convenience sampling method; accordingly, they were randomly allocated to the experimental and control groups. The experimental group underwent ten 90-minute weekly sessions of group schema therapy. The research instruments included the 75-item Early Maladaptive Schema Questionnaire-Short Form, the Connor-Davidson Resilience Scale, and the Ryff's Scale of Psychological Wellbeing. Data analysis was conducted by Multivariate Analysis of Covariance (MANCOVA) using SPSS. Results: The obtained results revealed that group schema therapy was effective in promoting psychological wellbeing and resilience in individuals under treatment with methadone and buprenorphine (P<0.01).  Conclusion: This study provided evidence for the effectiveness of group schema therapy in enhancing psychological wellbeing and resilience among individuals with substance dependence. This intervention program can thus be implemented by substance dependence therapists and psychiatric nurses.